"A place at the table:" a qualitative analysis of community board members' experiences with academic HIV/AIDS research. Issue 1 (December 2016) - Safo, Stella; Cunningham, Chinazo; Beckman, Alice; Haughton, Lorlette; Starrels, Joanna
Abstract Background Community advisory boards (CAB) are proposed as one mechanism to carry out successful community based participatory research (CBPR), but the presence of CABs may be insufficient to optimize academic-community partnerships. Methods We conducted semi-structured interviews with minority members of a CAB partnered with a HIV/AIDS research center and identified three themes. Results First, lack of trust in researchers included two subthemes: researchers' lacked respect for community-based organizations' (CBO's) interests and paid inadequate attention to building trust. Second, power imbalance included three subthemes: CAB members felt like inferior "token" members, felt that a lack of communication led to disempowerment, and held preconceived beliefs of researchers that led to perceived power imbalance. Third, CAB members suggested best practices, including using collaborations to build trust, actively allocating power, and sharing tangible research benefits with CBOs. Conclusions Our findings indicate that CABs must be founded on trust and instilled with power to meet the tenets of CBPR.